COMPARATIVE CLINICAL EVALUATION OF CAUDAL BUPIVACAINE VERSUS BUPIVACAINE PLUS TRAMADOL FOR PEDIATRIC INFRAUMBILICAL SURGERIES: A STUDY ON POSTOPERATIVE ANALGESIA - AYUSHEE KHANDELWAL; RASHMI GUPTA; SURESH PANDEY (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Effective post-operative pain management is crucial in pediatric patients undergoing infraumbilical surgeries. Various regional anesthesia techniques, including caudal block, have been used to provide post-operative analgesia in children. The addition of tramadol, a synthetic opioid analgesic, to bupivacaine in caudal anesthesia has shown potential benefits. This study aims to compare the clinical efficacy of single-shot caudal bupivacaine alone versus bupivacaine plus tramadol for post-operative analgesia in pediatric infra-umbilical surgeries. Methods: A prospective, randomized, double-blinded clinical study was conducted at our institute. The present study will be carried out in 60 pediatric patients of the American Society of Anesthesiologists Grades I and II between the age of 1 and 8 years, undergoing infraumbilical surgeries. These children were randomly divided into 2 groups. Group B (n=30) received caudal block with 0.25% bupivacaine (1 mL/kg) and Group BT (n=30) received caudal block with 0.25% bupivacaine (1 mL/kg) with tramadol (1 mg/kg). The variables studied were hemodynamic changes, duration of analgesia, and incidence of side effects. Pain assessment was done at 1, 2, 3, 4, 8, 12, and 24 h post-operatively using modified objective pain scale. Results: It was observed that the mean duration of analgesia in Group BT (9.05±2.21) h was significantly longer (p=0.0001) than Group B (3.78±0.94) h. Hemodynamic parameters remained comparable during intraoperative and post-operative periods. There was no incidence of nausea, vomiting, bradycardia, hypotension, pruritus, or decrease in respiratory rate in the two groups. Conclusion: In our study, we concluded that a single-shot caudal block with 0.25% bupivacaine (1 mL/kg) plus tramadol (1 mg/kg) resulted in longer duration of analgesia when compared to 0.25% bupivacaine (1 mL/kg) alone with no incidence of any side effects.